Review of the Applicability of Advocate Immunity Rights in Indonesia : A Comparative Study with the Australian Solicitor - Siagian, Fahrizal S.; Lubis , Andi Hakim; Firouzfar, Saied (Neoclassical Legal Review: Journal of Law and Contemporary Issues, 2022)
Advocates are one part of the Law Enforcement Officers who have rights and obligations that must be obeyed by each party. Advocate Immunity Rights which is a right that states advocates cannot be prosecuted civilly or criminally in carrying out their professional duties in good faith for the benefit of client defense. Problems are how is the influence of legal sociology in supporting the professional duties of advocates? and how is the applicability of advocate immunity rights in accordance with the indonesian advocates law and the australian solicitor studied based on legal compliance theory? The purpose of this study is to answer the various problems of this research. Normative juridical method with a comparative study approach in Indonesia and Australia. The essential influence of legal sociology in supporting the professional duties of advocates is because advocates will be faced with diverse community cultures. Legal compliance theory of advocate immunity rights in accordance with Advocate Law Number 18 of 2003 is still often ignored by other law enforcement officials. Advocates are still often criminalized in carrying out professional duties, namely defending their clients, unlike in Australia which prioritizes immunity rights. This is a special concern for each of the law enforcement institution to respect each other, in order to create fair law enforcement